The Missing Spark: Enhancing Parental Engagement in Punjab’s Early Childhood Education Programs - Qayyum, Abdul; Saeed, Amber; Qureshi, Abrar Hussain (Pakistan Languages and Humanities Review, 2024)
This qualitative research explored parental roles in Early Childhood Education (ECE) programs within Jhang and Dera Ghazi Khan Districts of Punjab, Pakistan. It aimed to understand family perspectives on program effectiveness and parental engagement in public schools. Parental involvement is crucial for a child’s educational success. However, concerns exist regarding family engagement in Pakistani public schools, particularly within ECE programs. Semi-structured interviews were conducted with twelve parents from both rural and urban areas of Punjab. Interviews focused on parental perspectives on ECE programs, their level of engagement in schools, and factors influencing participation. Findings revealed a strong parental preference for high-quality ECE programs and supportive learning environments. However, parents expressed concerns about a perceived lack of teacher enthusiasm and communication regarding their children’s progress. While acknowledging the importance of play in learning, a lack of adequate play spaces was also noted. These findings highlight the need for improved educational practices and enhanced collaboration between parents and educators. Schools should prioritize providing regular updates on children’s progress and consider creating stimulating learning environments with dedicated play spaces to foster active learning within ECE programs. This study offers valuable insights for promoting more effective parental engagement in their children’s early education.